The Overview of the Nurse’s Discharge Planning Implementation in Children with ARI in Indonesia : Literature Review - Natasya Dinda; Lantin Sulityorini; Ira Rahmawati (KHD-Production, 2022)
Implementation of discharge planning in children with ARI (Acute Respiratory Infection) in Indonesia is one of the efforts to prevent recurrent ARI in children. This study aimed to identify the implementation of discharge planning in children with ARI in Indonesia. A literature review searched four databases (Google Scholar, Science Direct, PubMed, and Springer) for all studies design between 2016-2021. The Prisma checklist guided in this review, title, abstract, full-text, and methodology were assessed for the eligibility of studies. The researcher found ten studies that met inclusion criteria in the review. Included studies consist of three studies discussing the factors that cause ARI, five studies discussing the implementation of discharge planning, and two studies of both. The average number of participants is 95 and most of the study design in this study used cross-sectional. 1) the importance of knowledge about the risk factor of ARI for discharge planning; 2) the risk factors of ARI in children, such as nutrition status, birth weight, exclusive breastfeeding, parental smoking status, dwelling density, ventilation, and humidity; 3) the implementation of discharge planning in the pediatric room was unoptimally implemented; 4) factors that causing unoptimally implementation of discharge planning are knowledge, competency, and coordination of nurse. It is also the competency of parents, especially mothers, in caring for children with ARI in Indonesia. Keywords: Acute Respiratory Infection, Discharge Planning, Children